The prophylactic effect of a Eugenia aquea extract against oxidative stress and inflammation associated with the development of arthritis in an adjuvant-induced arthritis rat model. Issue 12 (4th December 2018) - Abd El-Ghffar, Eman A.; Eldahshan, Omayma A.; Barakat, Alaa; Efferth, Thomas
Abstract : Rheumatoid arthritis (RA) is the most common human autoimmune disease. Abstract : Rheumatoid arthritis (RA) is the most common human autoimmune disease. A petroleum ether extract of Eugenia aquea ( E. aquea ) was analyzed by GC/MS. Antioxidant and anti-inflammatory activities were investigated in rats with adjuvant-induced arthritis (AIA). An AIA rat model received orally/daily a vehicle, diclofenac (100 mg per kg b.w.), and E. aquea extract (50 or 100 or 200 mg per kg b.w.; for 21 days). Fifty-five out of 70 compounds (97.77%) were identified: eucalyptol (34.14%), α-pinene (15.91%), l -verbenone (8.01%), camphor (7.38%) and borneol (6.74%). In an acute oral toxicity study, the E. aquea extract did not show any toxic effects in rats at 2000 mg/ kg −1 . Only a high dose of the E. aquea extract or diclofenac significantly alleviated ( P < 0.05–0.001) all complications observed in arthritic rats, including body weight loss, articular/extra-articular oxidative injury and synovial joint inflammation by increasing food intake as well as improving the antioxidant defense system and inflammatory marker. The dose-dependent modulatory activity of the E. aquea extract was statistically significant. It was equivalent to and sometimes even better than that of diclofenac. The present study proved the antioxidant and anti-inflammatory activities of the E. aquea extract, which could be attributed to the presence of eucalyptol and α-pinene.